Çimento esaslı kompozit plakalarla güçlendirilmiş bölme duvarlarının kayma dayanımının belirlenmesi - Gür, Mustafa (Deprem Mühendisliği ve Afet Yönetimi Enstitüsü, 2017)
Yakın tarih boyunca meydana gelen çok sayıda yıkıcı depremler farklı ülkelerde yüzbinlerce insanın yaşamını yitirmesine ve milyonlarca insanın da evlerini kaybetmesine neden olmuştur. Dünya üzerinde, doğal afetler içerisinden depremin en etkili olduğu ülkelerden birisi de Türkiye’dir. Türkiye çok önemli bir deprem kuşağında yer almaktadır. Dünyanın en aktif fay hatlarından biri olan Kuzey Anadolu Fay Hattı başta olmak üzere Doğu Anadolu Fay Hattı, Batı Anadolu Fay Hattı ve birçok fay hattı ülkemizde bulunmaktadır. Dolayısıyla, yapılan yapıların projelendirilmesinden bitimine kadar olan süreçte deprem etkisini karşılayabilecek düzeyde olması gerekir. Gelişmiş ülkelerde, depremden kaynaklanan can ve mal kayıpları önemli ölçüde azaltılmıştır ve ilgili yönetmeliklerde deprem etkisini karşılayabilecek tasarımlar mevcuttur. Ülkemizde ise deprem risklerinin azaltılması konusunda 17 Ağustos 1999 tarihinde yaşanan büyük felaketten sonra detaylı incelemeler ve önemli çalışmalar yapılmıştır. Bu çalışmalardan bir tanesi ise kolon ve kirişlerden oluşan betonarme çerçeve ile sınırlandırılmış bölme duvarlarının çeşitli yöntemlerle güçlendirilmesidir. Yapılan araştırmalar, betonarme çerçeve içerisinde bulunan bölme duvarlarının betonarme taşıyıcı sistemin rijitliğini ve yatay yük taşıma kapasitesini artırdığını göstermektedir. Daha öncesinde önemi üzerinde fazla durulmayan bölme duvarlarının 2007 Deprem Yönetmeliği’nde yapılan birtakım düzenlemeler ve eklemeler sonrasında taşıyıcı sistem üzerindeki katkısı dikkate alınmış ve söz konusu yönetmelikte çeşitli güçlendirme yöntemlerine yer verilmiştir. İçinde bulunduğumuz coğrafyanın tarihine bakılacak olursa yaşanan depremler içerisinde büyük ölçekli depremlerin dışında küçük ölçekli depremlerin de can ve mal kaybına neden olduğu görülmektedir. Bunun nedeni Türkiye’de bulunan mevcut yapıların çoğunun mühendislik hizmeti almamış olmasıdır. Bunun yanı sıra yapıların yapıldığı zamandaki ilgili yönetmeliklere ve standartlara uyulmayan üretimler veya yönetmeliklerdeki eksiklikler can ve mal kaybının artmasının diğer nedenleridir. Dolayısıyla, ülkemizdeki 1999 depremi öncesi yapılmış mevcut yapıların çoğu, mühendislik hizmeti görmediğinden ve denetimlerde ihmallerin olmasından, düşük dayanımlı beton ve yetersiz donatı ile inşa edilen yapılar olup, can ve mal kaybı için büyük risk taşımaktadırlar. Böyle bir durumda, deprem riskini ve can ve mal kaybını azaltmak için mevcut yapıların güçlendirilmesi, yapılacak yeni yapıların da deprem etkisini karşılayabilecek yeterli taşıyıcı sistem güvenliğine sahip olması gerekmektedir. Fakat ülkemizdeki mevcut yapılar dikkate alındığında, güçlendirme işlemleri ciddi ekonomik problemlere yol açacaktır. Bunun için, güçlendirme ihtiyacı olan yapıların güçlendirilmesinde, maliyetin önemli derecede düşük tutulması ve yeterli güvenliğin sağlanması gerekmektedir. İşte bu tez çalışmasında, zayıf yapıların depreme karşı güçlendirilmesinde farklı bir güçlendirme yöntemi oluşturmak, yeni yapılacak yapıların da deprem etkisi altındaki davranışlarının ve performanslarının, yeni bir güçlendirme yöntemi olan kompozit plakalarla güçlendirilen bölme duvarlarının artırılmış ilave katkılarıyla değiştirilmesi ve geliştirilmesi amaçlanmıştır. Bu amaç doğrultusunda, mevcut binaların ve inşa edilecek yeni binaların yatay etkiler açısından daha güvenli olması ve daha az işçilik gerektirmesi söz konusudur. Ayrıca ülkemizdeki gelişen sanayii ile birlikte yeni güçlendirme metotlarının daha ekonomik ve uygulanabilir olması hedefler arasındadır. Bu tez çalışması için İ.T.Ü. Yapı ve Deprem Mühendisliği Laboratuvarında deneysel olarak çalışılmıştır. Bu çalışma kapsamında, denenmek için 9 adet 760x760 mm ölçekli bölme duvar numuneleri üretilmiştir. Üretilen bu numunelerden bazıları çimento esaslı kompozitlerle (TRCC) güçlendirilmiş ve bu güçlendirme yönteminin dayanıma olan etkisi güçlendirilmeyen şahit numunelerle karşılaştırılarak incelenmiştir. Güçlendirme tekniği olarak kullanılan bu çimento esaslı kompozit (TRCC) malzeme, çimento harcı ve liflerden oluşan kare boşluklu yatay ve düşey doğrultuda dokunmuş ağ şeklinde özel tekstillerden oluşmaktadır. Bu çalışmada PVA (Polyvinyl Alcohol) ve AR Glass içerikli iki farklı tekstil kullanılmıştır. Bu sistemle üretilen kompozitlerin detaylı bir işçilik ve yüzey hazırlığı gerektirmemeleri, yanma dayanımlarının karbon elyafı, epoksi gibi malzemelere göre yüksek olması, güve, bit, mantar vs. ye karşı dirençli olmalarından dolayı dayanımlarında herhangi bir azalmanın olmaması, kopma ve yırtılmalara karşı dayanıklı olmaları, özellikle nem gibi atmosferik koşullardan etkilenmemeleri, ara yüzeylerde yapışma özelliklerinin iyi olması gibi avantajları vardır. Kompozit malzemenin yapımında kullanılan çimento hamuru ise belli oranlarda çimento, kum, su, akışkanlaştırıcı, silis dumanı, uçucu kül, defoamer ve polimer içermektedir. Ayrıca bölme duvarların güçlendirilmesinde kullanılan TRCC sistemler, duvarlar deneye tabi tutulduğunda plakaların basınçla patlayarak deney sonuçlanmadan kopmasını engellemek için tüm kenarlarından 10~15 mm boşluk bırakılarak duvarlara yapıştırılmıştır. Diyagonal olarak deneye tabi tutulan numunelerin basınç yükünü sağlıklı bir şekilde iletmeleri için de düşey yüke maruz kalan köşegenlere beton başlıklar yapılmıştır. Malzemelerle ilgili yapılan deneysel çalışmalar iki aşama halinde gerçekleştirilmiştir. İlk aşamada bölme duvarlar üzerine yapıştırılacak kompozit plakalar üretilmiştir. Sonraki aşamada ise boşluklu tuğlalar kullanılarak 760x760 mm boyutundaki duvar numuneleri üretilmiştir. Üretilen TRCC plakalarla farklı şekillerde güçlendirilen bu bölme duvarların şahit numunelere ve birbirlerine göre kayma dayanımlarındaki, kayma şekil değiştirmelerindeki ve kayma modüllerindeki değişmeler (artışlar ve azalışlar) incelenmiştir.

Numerous destructive earthquakes occurred during recent history have caused hundreds of thousands people to lose their lives and millions people being homeless in different countries. Around the world, Turkey is one of the countries where earthquake is the most effective within the natural disasters. Turkey is located in a very important earthquake zone. Particularly North Anatolian Fault Line, East Anatolian Fault Line, Western Anatolian Fault Line and many other fault lines are located in our country. Therefore it must be at a level that can meet the effect of earthquake in the process from the designing of the structures to the end. In developed countries, life and property losses because of the earthquakes are significantly reduced and there are designs that can meet the earthquake effect in the related regulations. On the other hands, after the great disaster that occured on 17 August 1999, detailed and important studies were conducted in order to reduce the earthquake risks in our country. One of these studies is strengthening of infill walls delimited by reinforced concrete frame consisted of columns and beams by various methods. The investigations show that infill walls inside the reinforced concrete frame increase the rigidity and horizontal load carrying capacity of the reinforced concrete structural system. Infill walls, previously with lower priority, were taken into account in the 2007 Turkish Seismic Code by contribution to carrier system and the Code includes different strengthening methods. If we look at the history of the geography we are in, it is seen that besides large-scale earthquakes, small-scale earthquakes also have caused the losses of life and property within the earthquakes taken place. The reason for this is that existing structures in Turkey have not received engineering services. In addition to this, deficiencies in regulations or productions that do not comply with the relevant regulations and standards at the time of construction are other causes of increased loss of life and property. Therefore, most of existing structures built before the earthquake in 1999 in our country were constructed with low-strength concrete and inadequate reinforcement and have great risk for loss of life and property because they do not provide engineering services and there are vitally negligence in audits. In such a case, existing structures should be strengthened in order to mitigate earthquake risk and loss of life and property, and new structures to be constructed should have sufficient carrier system safety to meet the earthquake effect. However, given the existing structures in our country, the strengthening will lead to serious economic problems. For this reason, while the structures that need reinforcement are strengthened, it is necessary to keep the cost considerably low and ensure adequate safety. In this thesis, it is aimed to construct a different strengthening method in strengthening weak structures against earthquake, to make new structures in a shorter time, to be safer and to be economically less costly. Also it is aimed to change and improve the behaviours and performances of the new buildings due to the earthquake with the additional contributions of infill walls strengthened by composite plates which is a new strengthening method. To this end, existing buildings and new buildings to be built are expected to be safer and require less labor in terms of horizontal loads. In addition, it is expected that new strengthening methods will be more economical and feasible with the developing industry in our country. The most important composite materials used in Civil Engineering applications are reinforced concrete. The combination of high compressive stress of the concrete and the high tensile stress of the reinforcement provides an appropriate load carrying capacity in reinforced concrete systems. On the other hand, textile-reinforced composite materials allow the production of thin-walled reinforced concrete elements with high compressive and tensile strength. In recent years, TRCC systems have become attractive with the high performance they provide within cement based composites. These textile-reinforced concretes have better and more homogeneous structure than ordinary concretes and provide good performance with high strength and improved durability characteristics. The textiles can significantly increase the mechanical behaviour of cement matrices under static and dynamic conditions and provide protection against effects of superior tensile strength, toughness, ductility, energy absorption and environmental degradation. Cementitious composites containing textiles have higher strength and they are more effective when compared to randomly dispersed short fibers into the concrete. These textiles have advantages such as good adherence, easy application and working in harmony with cement mortar. In this thesis, polyvinyl alcohol (PVA) and alkali resistance glass (AR Glass) textile systems are used in the production of cementitious composite plates. AR Glass textile has a more brittle structure while PVA is more ductile. Therefore PVA textile has more energy absorption capacity and its contribution to strength is more. However, in PVA textiles, it is not easy to pass the cement mortar through the voids because the filaments forming the fabric are knitted tightly. This sometimes causes the composite material not to work properly. However, the use of textiles in cementitious composite materials provides higher ductility and tensile strength than glass fiber reinforced concrete and other fiber-containing composites. This thesis has been experimentally studied in Istanbul Technical University, Earthquake and Structural Engineering Laboratory. For this study, 9 pieces of 760x760 mm sized infill wall specimens were produced for testing. Some of these specimens were reinforced with cement based composites (TRCC) and the effect of this strengthening method was examined by comparing with the non-reinforcing test specimens. This cement-based composites used as a strengthening technique consists of cement mortar and special fibrous textiles woven in horizontal and vertical direction with square space. Two different textiles, PVA (Polyvinyl Alcohol) and AR Glass, were used in this study. The composites produced with such a system have advantages such as no need for detailed workmanship and surface preparation, having higher fire resistance compared to materials such as carbon fiber and epoxy, no reduction in strength due to their resistance to lice, moth, fungus etc. being resistant to rupture and tearing, not to be affected by atmospheric conditions, especially humidity, having strong adhesion on interfaces. Cement paste used in the production of composite plates includes cement, sand, water, silica fume, plasticizer, fly ash, defoamer and polymer at certain ratios. In addition, TRCC systems were applied on the partition walls with 10~15 mm gaps from all sides so that the plates did not breake before the end of the experiment when the infill walls were tested. Experimental studies on materials have been carried out in two stages. In the first stage, composite plates to be bonded on infill walls were produced. The production of these composite plates was carried out in Istanbul Technical University, Composite Structures Laboratory. A total of 48 pieces of plates were produced. A new system was applied for these productions. In this system, the textile was placed on a rotating band and the cement mortar pre-placed into the reservoir located on the machine was poured over the textile while in motion. Textile was wrapped on a metal slab 4 times or 6 times by applying tension on textile. The plates removed from the formwork after one day were cured in water for strengthening. Eventually, the plates were cut in 360x360 mm dimensions to be applied on the infill walls. In the next stage, 760x760 mm wall specimens were produced using hollow bricks. The infill walls were built in 4 rows with 4 bricks in a row. After the first row is completed, the second row starts with half brick. The reason of this is that the bricks do not overlap and so they are not separated from each other because they work in harmony with each other. The joint gaps left between the bricks are 10~15 mm. After the produced wall specimens gain strength for about a week, notches were made on the walls to provide better adherence between the cement mortar used to bond the plates and the wall. Then the plates were adhered on the wall specimens and held for 28 days to gain enough strength. In the final stage, the wall samples placed diagonally in the testing machine were tested under compressive loads. The changes (increase and decrease) in the shear strength, shear deformation and shear modulus of these infill walls differently strengthened with produced TRCC plates in comparison with the reference specimens were analysed.
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Deprem Mühendisliği ve Afet Yönetimi Enstitüsü, 2017
Thesis (M.Sc.) -- İstanbul Technical University, Institute of Earthquake Engineering and Disaster Management Sciences, 2017
Keywords: Duvarlar; Kompozit gereçler; Tuğla duvarlar; Duvarcılık; Polimerler; Yapı iskeletleri; Deprem etkileri; Walls; Composite materials; Brick walls; Masonry; Polymers; Structural frames; Earthquake effects